2007
DOI: 10.1016/j.tra.2006.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the propensity to cycle to work

Abstract: This paper describes the development of a mode choice model for the journey to work with special emphasis on the propensity to cycle. The model combines revealed preference (RP) and stated preference (SP) data to form a very large and comprehensive model. RP data from the National Travel Survey was combined with a specially commissioned RP survey.A number of SP surveys were also undertaken to examine the effects of different types of en-route and trip end cycle facilities and financial measures to encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(181 citation statements)
references
References 11 publications
4
156
0
9
Order By: Relevance
“…Ironically, Berlin owes its bicycle friendly urban form to planning agendas either contrary to, or detached from, cycling promotion. Studies suggest that in the context of low bicycle use (as Berlin had until the 1990s), segregated cycle lanes can nurture increased levels of cycling participation to a significant extent (Wardman et al, 2007;Tilahun et al, 2007). Given an inherited urban form conducive to high cycling rates-wide spacious streets, extensive segregated cycle infrastructure, and prevalent cycling appropriate journey lengths -pre-existing urban form seems to have played a key role.…”
Section: Re-examining Berlin's Cycling Transitionmentioning
confidence: 99%
“…Ironically, Berlin owes its bicycle friendly urban form to planning agendas either contrary to, or detached from, cycling promotion. Studies suggest that in the context of low bicycle use (as Berlin had until the 1990s), segregated cycle lanes can nurture increased levels of cycling participation to a significant extent (Wardman et al, 2007;Tilahun et al, 2007). Given an inherited urban form conducive to high cycling rates-wide spacious streets, extensive segregated cycle infrastructure, and prevalent cycling appropriate journey lengths -pre-existing urban form seems to have played a key role.…”
Section: Re-examining Berlin's Cycling Transitionmentioning
confidence: 99%
“…Too dangerous, lack of sufficient fitness, lack of motivation, lack of facilities at work (showers, bike racks, etc. ), no bike lanes, personal safety during journey, bad weather, lack of proper lighting, distance, topography, lack of safe parking at destination, lack of cycling knowledge or experience, too much traffic, uncomfortable, difficulties with trip chaining, need to carry things, air pollution, free car parking at work, lack of time, and bad road conditions (3,4,6,9,16,(18)(19)(20)(21)(22).…”
Section: Cycling Habits and Other Psychological Variables Affecting Cmentioning
confidence: 99%
“…Wardman et al examined revealed and stated preferences of cyclists in the United Kingdom and found that their participants currently used few bicycle lanes to bicycle to work, but that this was generally because the lanes were not available for use. Respondents indicated that more on-road bicycling facilities would encourage them to bicycle more (10). In their random-sample survey of Portland, Oregon, residents, Dill and Voros found that nearly 40% of people who wanted to bicycle more cited a lack of bike lanes or trails as a barrier to doing so (11).…”
Section: Literature Reviewmentioning
confidence: 99%